"I Am Starting to Believe in the Word 'Justice'": Lessons from an Ethnographic Study on Community Courts. (8th August 2020) - Gal, Tali; Dancig-Rosenberg, Hadar
Abstract: With the growing awareness of the crisis of mass incarceration and distrust toward the legal system, recent years have seen a rise in interest in specialized, problem-solving, and therapeutic courts designed to reduce incarceration and recidivism rates and enhance public trust in state authorities. Community courts have been operating in numerous jurisdictions worldwide, providing a non-adversarial platform in which repeat low-level offenders are offered a comprehensive rehabilitative and restorative intervention program. Alongside evaluations demonstrating the ability of community courts to reduce incarceration and enhance offenders' trust, some critics have suggested that community courts jeopardize offenders' procedural rights and result in over-criminalization of program non-completers. This Article provides a qualitative empirical examination of an Israeli community court model, inspired by the Red Hook Community Justice Center in Brooklyn, New York. Based on over 280 hours of observations of approximately 100 hearings and fourteen staff meetings, the findings provide an inside look at the ways in which Israeli community courts implement a range of evidence-based, democracy-oriented approaches to crime control, such as procedural justice, therapeutic jurisprudence, and community justice, in the context of community courts. The findings also point to a need to pay closer attention to how these courts continue their operation, within a broader adversarial legal framework of criminal justice. The challenges identified in this Article raise questions that are relevant to other community courts in the United States and elsewhere.